2015
DOI: 10.1159/000369755
|View full text |Cite
|
Sign up to set email alerts
|

MiR-144 Inhibits Proliferation and Induces Apoptosis and Autophagy in Lung Cancer Cells by Targeting TIGAR

Abstract: Background: MiRNAs are noncoding RNAs of 20-24 nucleotides that function as post-transcriptional negative regulators of gene expression. MiRNA genes are usually transcribed by RNA polymerase II in the nucleus. Their initial products are pre-miRNAs which have cap sequences and polyA tails. The p53-induced glycolysis and apoptosis regulator (TIGAR) was discovered through microarray analysis of gene expression following activation of p53. However, little is known about the effect of miR-144 on cell proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 41 publications
(41 reference statements)
3
60
0
Order By: Relevance
“…A previous study found that over-expression of miR-144 suppressed proliferation and promoted apoptosis and autophagy in LC cells by targeting the p53-induced glycolysis and apoptosis regulator, which was consistent with our results [38]. When ERS was inhibited by 4-PBA, the autophagy factors and apoptotic factors also in turn displayed reduced levels.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study found that over-expression of miR-144 suppressed proliferation and promoted apoptosis and autophagy in LC cells by targeting the p53-induced glycolysis and apoptosis regulator, which was consistent with our results [38]. When ERS was inhibited by 4-PBA, the autophagy factors and apoptotic factors also in turn displayed reduced levels.…”
Section: Discussionsupporting
confidence: 92%
“…As lung cancer is associated with the dysregulation of signalling pathways associated with various cellular processes, such as cell cycle progression, cell proliferation and apoptosis, and angiogenesis, researchers have expended considerable effort to identify new agents capable of targeting these pathways as a means of achieving greater therapeutic benefits [8-10]. However, clinical trials have demonstrated that targeting these pathways individually exerts limited effects [11], which may be due to the heterogeneous nature of lung tumours.…”
Section: Introductionmentioning
confidence: 99%
“…In different types of cancers, downregulation of miR-144 has been observed, such as osteosarcoma and mesothelioma, indicating that miR-144 may be a potential tumor suppressor (17,18). Studies have revealed that miR-144 exerts its biologic functions by targeting the 3 0 untranslated region (UTR) of the mRNAs of a number of oncogenes, such as ROCK1 (19), ZEB1 and ZEB2 (20), ADAM (21), TIGAR (22), and c-MET (23). However, whether miR-144 regulates BCL6 in carcinogenesis has not been investigated.…”
Section: Introductionmentioning
confidence: 99%